Insight the effect of crystallinity of natural graphite on the electrochemical performance of reduced graphene oxide - Weijun Peng; Guihong Han; Yanfang Huang; Yijun Cao; Shaoxian Song (Results in Physics, 2018)
The effects of the crystallinity of natural graphites on the electrochemical performance of the resulting reduced graphene oxides (RGOs) were systematically researched. Electrochemical measurements were first carried out to characterize the electrochemical performances of the RGOs. The results showed that the RGO prepared from flaky graphite (FG) hold the best electrochemical performance with the greatest specific capacitance, the smallest charge transfer resistance (Rct), the best capacitive behavior, and the lowest ions diffusion resistance in comparison with the other RGOs synthesized from natural lumpy graphite (LG) and amorphous graphite (AG) under the same conditions. Furthermore, XPS and Raman analysis were conducted to scientifically explain the phenomena. The results illustrated that RGO prepared from FG (FRGO) hold the highest reduction degree, the greatest size of the in-plane sp2 domains, and the fewest defects, leading FRGO to hold the best electrochemical performance. The crystallinity of natural graphite affected the microstructure of the resulting RGO by influencing its oxidation, exfoliation and chemical reduction process, and then indirectly controlled the electrochemical properties of the RGO. Keywords: Reduced graphene oxide, Natural graphite, Crystallinity, Electrochemical performance